1987
DOI: 10.1203/00006450-198711000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Humoral and Cell- Mediated Immunity in Down Syndrome Children Living at Home

Abstract: ABSTRACT. Abnormalities of humoral and cell-mediated TC, T cells immunity have been described in Down syndrome but HC, helper cells reported findings have been inconsistent. Confounding fac-SC, suppressor cells tors have included age, institutional versus home life, hepatitis B antigenemia, and zinc deficiency. To clarify this problem, we studied 64 children with Down syndrome (DS) compared with an age-matched control group. All children had always lived at home. All the DS children were negative for hepatitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 22 publications
2
29
0
2
Order By: Relevance
“…Studies on the adaptive immune system of DS have shown that total lymphocyte numbers are decreased in this population (8)(9)(10)(11)(12)(13)(14). This holds true for the CD4 + and CD8 + T cell subsets, especially in the first 2 y of life, but becomes less pronounced with increasing age and eventually normalizes around the age of 16 y. Subdivision of T cells into naive and memory cells showed that in fact only the naive subsets are smaller compared with healthy controls (8,9,(11)(12)(13).…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Studies on the adaptive immune system of DS have shown that total lymphocyte numbers are decreased in this population (8)(9)(10)(11)(12)(13)(14). This holds true for the CD4 + and CD8 + T cell subsets, especially in the first 2 y of life, but becomes less pronounced with increasing age and eventually normalizes around the age of 16 y. Subdivision of T cells into naive and memory cells showed that in fact only the naive subsets are smaller compared with healthy controls (8,9,(11)(12)(13).…”
mentioning
confidence: 79%
“…This holds true for the CD4 + and CD8 + T cell subsets, especially in the first 2 y of life, but becomes less pronounced with increasing age and eventually normalizes around the age of 16 y. Subdivision of T cells into naive and memory cells showed that in fact only the naive subsets are smaller compared with healthy controls (8,9,(11)(12)(13). In contrast, the fraction of CD8 + T cells within the T cell compartment is increased, and the fraction of CD4 + T cells decreased (9).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Different aspects of the immune system have been studied in DS to obtain a better understanding of the increased risk of infection observed in affected individuals (4). Abnormalities in humoral and cell-mediated immunities and in phagocytic function have been reported (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…388,390 Increased IgG and decreased IgM levels may occur during late childhood and adolescence. 391 The thymus may be small, with marked thymocyte depletion and an increased number of Hassall's corpuscles.…”
Section: Immune Deficiency and Chromosomal Abnormalitiesmentioning
confidence: 98%